Factors associated with abstinence after a recent smoking cessation attempt across 28 European Union member states - Cheung, Chung-Mei M. (Tob Prev Cessat, 2020)
INTRODUCTION: There is a lack of information regarding factors associated with successful smoking cessation on a population and European Union (EU)-wide level. Our study seeks to explore individual and country-level factors associated with abstinence after a recent smoking cessation attempt across the EU. METHODS: We obtained data from the March 2017 Special Eurobarometer 87.1 (n=27901). Regression analysis was performed on a subset of 1472 individuals who made quit attempts in the past 12 months. Sociodemographic, policy and country-level factors were assessed using logistic regression among smokers and ex-smokers who attempted to quit approximately 12 months before the survey date. We defined and examined the Cessation Ratio (ratio of number of recent quitters to those who did not succeed) across 28 EU Member States. RESULTS: In all, 14.9% (n=1018) of current smokers and 8.80% (n=454) of ex-smokers attempted to quit in approximately the last 12 months (n=1472). Cessation Ratios ranged from 0.182 (95% CI: 0.045–0.319) in Estonia to 1.060 (95% CI: 0.262–1.860) in Sweden. There is a quadratic, U-shaped relationship between odds of quitting and smoking prevalence. The lowest odds of cessation were observed at a prevalence of 26.3%, with higher odds of cessation observed above and below this point. Respondents who reported financial difficulties were less likely to quit (AOR=0.66; 95% CI: 0.52–0.83). There was no association of likelihood of success with other sociodemographic factors or the Tobacco Control Scale treatment score. CONCLUSIONS: These findings highlight a need for exploring reasons behind the variation in likelihood of abstinence following a recent quit attempt, in order to design policies targeted at population groups or countries that need greater support.